Celebrating the legacy of the Reformation - Forrest Benjamin K.; Celebrating The Legacy Of The Reformation; King, Kevin L., Dr.; Hindson, Edward E.; Forrest, Benjamin K.; Celebrating The Legacy Of The Reformation (Nashville, Tennessee : B & H Academic, 2019)
Christians today will find new cause to rejoice in what God did in the sixteenth century through weak and fallible men and women. His people sought to submit themselves to the Word of God and lead his followers in a godly and faithful response to the gospel of grace. The Reformation is not a dead movement but a living legacy that can still capture the imagination and encourage men and women in their own Christian discipleship.
Introduction: Let the hammers ring: The legacy of the Reformation for the church today and tomorrow / Edward E. Hindson -- Celebrating the theological legacy of the Reformation: What the Reformers thought they were doing / Timothy George -- The legacy of the printing press for the production and study of the Bible / Benjamin P. Laird -- The priesthood of all believers: Theological intent and subsequent practice / Stephen Brett Eccher -- John Calvin and penal substitutionary atonement / Paul Owen -- Celebrating the devotional legacy of the Reformation: Retrieving the Reformation for the flourishing of Evangelical spirituality / Nathan A. Finn -- Luther's theology of the cross as a model for sanctification / John McKinley -- Theodore Beza, Latin poetry, and personal worship / Michael Spangler -- Celebrating the legacy of Reformation catechesis and preaching: The confessing church / Joseph Pipa -- Reformed confessions and confessional faithfulness / Roger Schultz -- The legacy of the Heidelberg catechism / Adriaan C. Neele -- Luther and Calvin's theology of preaching / Benjamin B. Phillips -- The legacy and re-formation of Reformation preaching: A cry for renascence / Kevin L. King -- Celebrating the legacy of the missions and martyrs of the Reformation: The mangled narrative of missions and evangelism in the Reformation / Ray Van Neste -- The word of God as missional tinder of the Reformation / John D. Woodbridge -- Sola scriptura and the recovery of Bible translation in global mission / Edward L. Smither -- Church under the cross: Anabaptist theology of martyrdom / Rex D. Butler -- Appendices: Latin poetry -- Testimonies of the Anabaptist women martyred in the Reformation / Candi Finch.
Includes bibliographical references and indexes.
Keywords: Reformation